Colombian refugees in Ecuador: sampling schemes, migratory patterns and consequences for migrants. (1st January 2011) - Bilsborrow, Richard E.; Mena, Carlos F.; Arguello, Eduardo
Methods for the design of samples to collect data on migrants as 'rare elements' are applied to Colombians migrating to Ecuador. With an upsurge in violence in Colombia beginning in the late 1990s, Colombians fled in increasing numbers to Ecuador, especially to Sucumbios in the Ecuadorian Amazon, an area of extraordinary biodiversity. These migrants comprise both asylum-seekers and traditional economic migrants. Despite the large influx, they still constitute a tiny part of the Ecuadorian population, creating the need to use 'rare elements' sampling methods. A household survey was carried out in 2006 in the five provinces found (2001 census) to have the largest proportion of Colombians. The main probability sample was supplemented by a snowball sample, with problems encountered described, and lessons learned. Key findings are summarised, comparing Colombians migrating to Ecuador voluntarily and involuntarily. Environmental effects of these migrants are minimal as most move to urban areas.